Commemoration as conflict: space, memory and identity in peace processes - McDowell, Sara (Rethinking peace and conflict studies, 2014)
Introduction -- Landscapes of commemoration : the relationship between memory, place and space -- The promise of peace -- A war by other means? : commemorating conflict in the new Northern Ireland -- Contested visions : memory, space and identity in the Basque country -- Challenging the boundaries of the Sri Lankan state : memory-work and the battle to belong -- An intractable conflict and an irreconcilable past: contesting the "other" through commemoration in Israel/Palestine -- Preserving the past and shielding the future : political memories in the former Yugoslav countries -- "Till Jesus comes again" : consolidating narratives of the liberation struggle in post-apartheid South Africa -- Conclusion